Integrated body temperature detection system with smart touch device - Noor Naimah, Yunus @ Junus (2010)
Nowadays health is really important to everyone, since world has been attacked by lots of infected disease such as bird flu and H1N1. All people in the world are seeking the best solution to avoid that kind of infected disease. Integrate Body Temperature Detection System with Smart Touch Device is a system that is able to capture and store data from patients using sensor via wireless connection to the system. The patient needs to touch or put the finger on the Smart Touch Device. So, for in case of infected disease, the doctors or nurses no need to touch the patients. The sensor will connect to the system via wireless. This system is developed in order to help any hospital or health centre to manage the measurement of body temperature especially for Hospital Tengku Ampuan Afzan (HTAA). By developing this system, the management of hospital or health centre performs in systematic through its function requirements. The users of Integrate Body Temperature Detection System with Smart Touch Device are doctors and the patients of HTAA. This system was developed using Microsoft Visual Basic 6.0 and Microsoft Access 2003 as the database platform and the methodology used in developing this system is Extreme Programming (XP) and integrate with sensor.